PEMBELAJARAN MENULIS KEMBALI DONGENG YANG TELAH DIBACA DENGAN METODE KONSTRUKSIVISME DI MTS AL MUTTAQIN BUPER JAYAPURA - Supardi Supardi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study describes rewriting process of tale reproduction and attainment in reproduction of a tale using constructivism teaching tecniques.  This study used Classroom Action Researc design on two cycles. Students were asked to rewrite contents of the tales and edited the writing on its contents and language use.  Subject of the study was 25 eigth graders of MTs Almuttaqien Buper, Jayapura.  Data were writing texts on the tales produced by students and scores on the quality of the texts.  Findings of the study showed that in cycle I students’ writing production was short of content and outline resulting incomplete quality.  Competency standard achieved in cycle I was 64%, below minimum criteria of attainment.  In cycle II students achieved 84% on rewriting the tales, indicating higher achievement than minimum criteria 75%.  This means constructivism has been successfully increased students’ attainment on reproducing tales they read.